Environmental Reporting Disclosures Practices of Listed Ceramic and Cement Companies at DSE in Bangladesh (Global Journal of Management and Business Research, 2019)
This study attempts to investigate the environmental accounting disclosure reporting practices in annual report of listed ceramic and cement companies at Dhaka Stock Exchange (DSE) in Bangladesh. To derive the results, we had collected data from secondary source more specifically from annual report. Collected data are analyzed by using, with statistical tools and SPSS software. For testing hypothesis, we have conducted data analysis with regression model and ANOVA test. The study revealed that only 40% listed ceramic companies disclosed their environmental accounting disclosure reporting practices in annual report and 71.43% listed cement companies disclosed their environmental accounting disclosure reporting practices in annual report. Both from ceramic and cement companies, no one disclosed any monetary information about environmental accounting disclosure reporting practices in their annual report. From two sectors comparatively cement companies disclosed more environmental accounting disclosure reporting practices in annual report. Another investigation was done under this study and found that there is no significant relationship of extend of environmental disclosure with Earnings Per Share (EPS), Net Profit (NP), rate of Cash Dividend (CD),Total Assets (TA); and Net Asset Value per Share (NAPV).
Keywords: environmental disclosure; annual reports; ceramic and cement companies